Application of role-playing learning model to improve students' theater skills - Rahma Alfisah; Wida Rahayunigtyas (PT. Pena Produktif Kreatif, 2026)
This study aims to analyze the application of role-playing learning methods in improving students' theater skills. The study was conducted in class XI B of SMA Negeri 10 Malang using the Kemmis & Mc. Taggart Classroom Action Research (CAR) model consisting of two cycles. Each cycle involves four stages, namely planning, implementation, observation, and reflection. In cycle I, students are introduced to basic theater techniques and asked to practice acting techniques, as well as practice reading scripts together. In cycle II, students further practice basic theater techniques and do space processing (blocking) using the scripts that have been studied. The results of the study showed that although in cycle I students' scores were still below the KKM, after cycle II, there was a significant increase in students' ability to play roles according to the characters they played. In addition, the Role-Playing method has also proven effective in improving students' interpersonal communication and self-confidence. This study shows that the application of the role-playing method can improve students' theater skills, while also having a positive impact on their social and emotional development.